Recovery of molybdenum from simulated wastewater by arginine - Bu-Chan Zhou; Xiao-Jun Zheng; Wei-Jiang Chen; Qi Li; Zhi-Peng Lai; Miao-Miao Wang; Ming Chen (Desalination and Water Treatment)
The high-efficiency and environmentally friendly recycle for recovering molybdenum from molybdenum wastewater utilizing arginine was studied in this paper. The optimum experimental conditions were determined through single-factor experiment. When pH = 2.1, arginine dosage n (arginine) /n (Mo) = 1, the temperature was set at 25 ℃, the Mo concentration decreased from 19.19 g/L to 75.4 mg/L, and recovery ratio of Mo reached 99.61%. In the experiment of coexisting ions, the effects of Cl-, SO42-, CO32-, Na+, Ca2+, and Mg2+ on the recovery rate of Mo were relatively slight, but the inhibitory effects of PO43- and Fe3+ increased with their concentrations. Mo8O26−4, when combined with positively charged arginine, facilitated precipitation, and thereby achieving the goal of recovering molybdenum from molybdenum wastewater. The results showed that roasting the sediment at 600 ℃ for 2 h was a certain economic benefits method to obtain high purity of MoO3. This research provides a novel approach for the molybdenum wastewater recovery and treatment, boasting advantages such as improved recovery efficiency, reduced treatment costs, and simplified operation. It can be applied in the treatment and recovery of molybdenum wastewater and other industrial waste in the near future.